Description of Hemoglobin Levels in Patients With Pulmonary Tuberculosis in The Intensive Treatment Stage at RSUD Ciamis - Wilujeng, Endang Octaviana; Dewi, Ayu Ratna; Istianah, Euis Tia (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objectives: Tuberculosis is one of the leading causes of death in the world. Pulmonary tuberculosis is a chronic disease that infects the lungs caused by Mycobacterium tuberculosis and can affect hemoglobin levels to become anemic. Anemia occurs due to insufficient iron intake and the use of anti-tuberculosis drugs (OAT). Anemia is defined as reduced hemoglobin levels in the blood. Hemoglobin is a protein that contains iron in red blood cells. This study aims to determine the description of hemoglobin levels in patients with pulmonary tuberculosis in the intensive treatment stage at Ciamis Regional Hospital.Methods: This research method is descriptive. Data collection techniques were obtained from secondary data. Sampling was done by purposive sampling technique which recruited 31 patients with pulmonary tuberculosis to be used as respondents. Results: From this study, 19 (61%) samples with normal hemoglobin levels and 12 (39%) samples with low hemoglobin levels were obtained.Conclusion: Based on the results of the examination of hemoglobin levels in patients with pulmonary tuberculosis in the intensive treatment stage at Ciamis Hospital, most of them have normal hemoglobin levels.